Delaminating Intramyocardial Hematoma in Patients with Heart Failure with Reduced Ejection Fraction: а Series of Clinical Cases - A. F. Safarova; R. Kh. Useinova; Zh. D. Kobalava; L. V. Karapetyan (Рациональная фармакотерапия в кардиологии)
Delaminating intramyocardial hematoma (DIMH) is a rare and potentially life-threatening complication of acute myocardial infarction. Currently, only isolated reports of cases of myocardial dissection have been published, and until recently, the diagnosis of DIMH was carried out during autopsy or surgery. The article describes echocardiographic criteria and discusses some aspects of the therapy of this pathology. The description of clinical cases of noninvasive diagnosis of DIMH in men aged 60 and 62 years hospitalized with the clinic of decompensation of chronic heart failure is given. This complication in the presented patients was diagnosed using transthoracic echocardiography, thanks to which it was possible to identify the dissection of the myocardium, as well as to trace the dynamics of the organization of an intramyocardial hematoma into a parietal thrombus. Various approaches to patient management are demonstrated: conservative tactics allowed to successfully stabilize the course of chronic heart failure in the first patient, while the condition of the other required the transplantation of a donor heart a few months after discharge from the hospital.